POSITION OF THE DECREE OF THE PEOPLE'S CONSULTATIVE ASSEMBLY (TAP MPR) IN THE HIERARCHY OF LEGISLATION IN INDONESIA - Akbar, Aryo; Ibnususilo, Efendi; Taufiqurrahman, Faishal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The reinsertion of the People's Consultative Assembly Decree (Tap MPR) into the hierarchical system of Indonesian statutory regulations through Law Number 12 of 2011 concerning the Formation of Legislative Regulations, has caused several problems, namely: 1) The position of the MPR Tap in the hierarchy of statutory regulations. Invitation; and 2) Which state institution should be given the authority to test the MPR Decree. The research results show that the position of the MPR Decree in the hierarchy of laws and regulations in Indonesia is in a